Comparison of the neurotoxic and myotoxic effects of two Moroccan scorpion venoms and their neutralization by experimental polyclonal antivenom - Oukkache, Naoual; Ahmad Rusmili, Muhamad Rusdi; Othman, Iekhsan; Ghalim, Noreddine; Chgoury, Fatima; Boussadda, Lofti; Elmdaghri, Naima; Sabatier, Jean-Marc (Life Science Journal, 2015)
Aims: Scorpion venoms contain complex mixtures of molecules, including peptides. These peptides specifically bind to various targets, in particular ion channels. Toxins modulating Na+, K+, Ca2+ and Cl − currents were described from venoms. The Androctonus and Buthus geni of scorpions are widely distributed in Morocco. Their stings can cause pain, inflammation, necrosis, muscle paralysis and death. The myotoxicity is predominantly associated with neurotoxic effects and is a cause of mortality and morbidity. In this study, pharmacological effects of venoms were investigated in vitro on neuromuscular transmission. Main methods: Effects of Androctonus mauretanicus (Am) and Buthus occitanus (Bo) venoms were investigated using the chick biventer cervicis nerve-muscle preparations. The protective activity of antivenom was also 33 investigated. The antivenom was made from serum of horse that was hyperimmunizedwith Bo and Androctonus australis hector (Aah) venoms and one venom from Middle East species (Lq). The protective activity of the antivenom was assessed on the neuromuscular system by using stimulated chick nerve muscle. The results were compared with lethal activity neutralization in mice. Key findings: Am and Bo venoms contain myotoxins and postsynaptic neurotoxins. In agreement with lethal potencies of these venoms in mice, Am venom displays greater neurotoxicity and myotoxicity. The antivenom prevented lethality caused by Am, Bo and Aah venoms. The antivenom did not prevent toxic effects caused by Am venom whereas it neutralized Bo venom. Significance: Amand Bo venoms contain distinct toxins that are responsible for myotoxicity and neurotoxicity. It would be appropriate to add Am venom to produce more efficient antivenom.